Role of diffusion tensor imaging in analyzing the neural connectivity of the parieto-insular vestibular cortex in pusher syndrome: As case report. Issue 16 (April 2020) - Yeo, Sang Seok; Jang, Sung Ho; Oh, Seunghue; Kwon, Jung Won
Abstract: Rationale: Pusher syndrome is a disorder of postural control. It is associated with unilateral lesions on central vestibular system. In the current study, we attempted to identify and investigate neural connectivity of the parieto-insular vestibular cortex in a patient with pusher syndrome, using diffusion tensor imaging. Patient concerns: A 60-year-old male patient had left hemiplegia due to an infarction on right premotor cortex, primary motor cortex, corona radiata and temporal and occipital lobe. The patient had severe motor weakness in left upper and lower limb, left side neglect and significant pusher syndrome. Diagnosis: Patient was diagnosed with left hemiplegia due to an infarction in the right middle cerebral artery territory at the neurology department of a university hospital. Interventions: One patient and 5 control subjects of similar age participated. Diffusion tensor imaging data were acquired at 4-month and 12-month after the initial injury. Outcomes: Fractional anisotropy, mean diffusivity, and tract volume (TV) were measured. TV values in both affected and unaffected hemispheres of the patient were significantly decreased at 4-month compared to those of control subjects. In the unaffected hemisphere of the patient, TV value showed significant increase at 12-month compared to that at 4-month. Although the TV value at 12-month of the affected hemisphere was out of reference range, TV was considerably increased compared to that at 4-month. Mean values for fractional anisotropy or mean diffusivity in 2 hemispheres did not show significant difference compared to those of control subjects regardless of month. Lessons: Restoration of an injured projection pathway between the vestibular nuclei and parieto-insular vestibular cortex with recovery of pusher syndrome was found in a patient with stroke.